The Bastille Effect Transforming Sites of Political Imprisonment - Welch, Michael (University of California Press, 2022)
The "Bastille Effect" refers to the unique ways that former sites of political imprisonment are transformed, physically and culturally. In their afterlives, these sites represent sustained efforts to hold perpetrators accountable for state violence. For that narrative to surface, the sites must be cleansed of their profane past. In some cases, clergy are even enlisted to perform purifying rituals that grant the sites a new identity as memorials. Around the globe, carceral sites have been dramatically repurposed into places of enlightenment that offer inspiring allegories of human rights. Interpreting the complexities of those common threads, this book weaves together a broad range of cultural, interdisciplinary, and critical thought to offer new insights into the study of political imprisonment, collective memory, and post-conflict societies. "The scholarly work of Michael Welch is recognized for its blend of critical theory and human rights. The Bastille Effect is no exception. This book reveals the terrible depths- and pains-of political imprisonment." KIERAN MCEVOY, Queen's University, Belfast "With compelling case studies, this wide-ranging book expands the significance of human rights to political imprisonment, technologies of power, and the meaning of memory." DIEGO ZYSMAN QUIRÓS, University of Buenos Aires "Welch's highly original project on the afterlife of sites of political imprisonment throws new critical light onto the politics of punishment and represents an important contribution to the burgeoning study of comparative penality." TIM NEWBURN, London School of Economics